Building Human Capital for the Institutional Strengthening of the Nicaraguan Ministry of Health - Gordillo-Tobar, Amparo; Herrera, Emilce; Rodriguez, Evelyn (World Bank, Washington, DC, 2021)
The Nicaraguan Ministry of Health of through the Health Education Directorate implements the Guideline 8 of the National Health Policy, which states the development of Human Talent as an essential axis for transforming the National Health System, because human resources are the most decisive factor for bringing about changes towards an effective, efficient and humanized approach to care. To do so, it has formulated staff education and training programs to help improve and deepen continuously the Family and community health model (MOSAFC) healthcare delivery and management model. Through the technical and financial support of the strengthening the public health care system project, the Ministry of Health (MINSA) implements a health continuing education process that includes in-service training, public health system workers' knowledge update, and community network training for midwives and voluntary collaborators.